Elucidation of roles for vitamin B12 in regulation of folate, ubiquinone, and methionine metabolism - Romine, Margaret F; Rodionov, Dmitry A; Maezato, Yukari; Anderson, Lindsey N; Nandhikonda, Premchendar; Rodionova, Irina A; Carre, Alexandre; Li, Xiaoqing; Xu, Chengdong; Clauss, Therese R W; Kim, Young-Mo; Metz, Thomas O; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Only a small fraction of vitamin B12-requiring organisms are able to synthesize B12 de novo, making it a common commodity in microbial communities. Initially recognized as an enzyme cofactor of a few enzymes, recent studies have revealed additional B12-binding enzymes and regulatory roles for B12 Here we report the development and use of a B12-based chemical probe to identify B12-binding proteins in a nonphototrophic B12-producing bacterium. Two unexpected discoveries resulted from this study. First, we identified a light-sensing B12-binding transcriptional regulator and demonstrated that it controls folate and ubiquinone biosynthesis. Second, our probe captured proteins involved in folate, methionine, and ubiquinone metabolism, suggesting that it may play a role as an allosteric effector of these processes. These metabolic processes produce precursors for synthesis of DNA, RNA, and protein. Thereby, B12 likely modulates growth, and by limiting its availability to auxotrophs, B12-producing organisms may facilitate coordination of community metabolism.